Clinical Review of the Effects of Chukyu (spine-healing) Pharmacopuncture in the Treatment of Lumbago and Skelalgia Patients - Lee Yoo-Hwan; Kim Jung-Hee; Jeong Jae-Yeob; Lee Kyeong-A; Kim Cheol-Hong; Jang Kyung-Jun; Kim Won-Il; Kim Young-Gyun; Yoon Hyun-Min (Korean Pharmacopuncture Institute, 2012)
Objective:The purpose of this study is to report the effects of Chukyu (spine-healing) pharmacopuncture treatment in patients with lumbago and skelalgia. Methods:This clinical study included 45 patients who were treated for lumbago and skelalgia at the Department of Acupuncture and Moxibusition, Dong-Eui University College of Oriental Medicine, from July 5, 2011, to January 31, 2012. Subjects were randomly divided into two groups: Chukyu (spinehealing)- pharmacopuncture-treated group (experimental group, n = 23) and normal saline-pharmacopuncture-treated group (control group, n = 22). Patients in the experimental group were treated with acupuncture and Chukyu (spine-healing) pharmacopuncture while those in the control group were treated with acupuncture and normal saline pharmacopuncture. To estimate the efficacy of controlling pain, we checked the visual analog scale [VAS], and to estimate the improvement of the symptoms, we evaluated by pain rating scale [PRS] and the Oswestry low-back pain disability index [ODI]. Results:A comparison of the experimental and the control groups showed more significant improvements in the VAS, PRS, and ODI for the experimental group than for the control group. Conclusions:Chukyu (spine-healing) pharmacopuncture can be used for effective treatment in patients with lumbago and skelalgia.